Evaluation du risque de mort subite lié à lacardiomyopathie hypertrophique à Dakar - Simon, Antoine Sarr (Cardiovasc J Afr, 2018)
AIM: The aim of this study was to assess of the risk of sudden death in a population of hypertrophic cardiomyopathy patients in Dakar. METHODS: This was a transverse study at the cardiology clinic of Aristide Le Dantec Hospital from January 2014 to June 2015. We used the European Society of Cardiology risk score to calculate this risk. RESULTS: The average age of patients was 53 years. Unexplained syncope was found in two patients and two others had a family history of sudden death. The septal hypertrophy average was 20.9 mm. Seven patients had left intraventricular obstruction. One patient had a high risk of sudden death, three had intermediate risk and 13 had low risk. Competitive sport was not allowed, 13 patients were under medical treatment, one had an implantable cardioverter defibrillator and two had no treatment. CONCLUSION: Our study highlighted a low and intermediate risk of the occurrence of sudden death at five years. One patient had a high risk of sudden death.